Citizenship in Antiquity Civic Communities in the Ancient Mediterranean - Filonik, Jakub; Plastow, Christine; Zelnick-Abramovitz, Rachel (Taylor & Francis, 2023)
Citizenship in Antiquity brings together scholars working on the multifaceted and changing dimensions of citizenship in the ancient Mediterranean, from the second millennium BCE to the first millennium CE, adopting a multidisciplinary and comparative perspective. The chapters in this volume cover numerous periods and regions - from the Ancient Near East, through the Greek and Hellenistic worlds and pre-Roman North Africa, to the Roman Empire and its continuations, and with excursuses to modernity. The contributors to this book adopt various contemporary theories, demonstrating the manifold meanings and ways of defining the concept and practices of citizenship and belonging in ancient societies and, in turn, of non-citizenship and non-belonging. Whether citizenship was defined by territorial belonging or blood descent, by privileged or exclusive access to resources or participation in communal decision-making, or by a sense of group belonging, such identifications were also open to discursive redefinitions and manipulation. Citizenship and belonging, as well as non-citizenship and non-belonging, had many shades and degrees; citizenship could be bought or faked, or even removed. By casting light on different areas of the Mediterranean over the course of antiquity, the volume seeks to explore this multi-layered notion of citizenship and contribute to an ongoing and relevant discourse. Citizenship in Antiquity offers a wide-ranging, comprehensive collection suitable for students and scholars of citizenship, politics, and society in the ancient Mediterranean world, as well as those working on citizenship throughout history interested in taking a comparative approach.